Analysis And Recommendations For Redesigning User Interface In Travelaja Application Using The User Centered Design Method - Fairuz Abid Insanullah; Mira Kania Sabariah; Veronikha Effendy (Syntax Corporation, 2022)
The TravelAja application is mobile commerce that aims to serve online travel booking services. This application has a basket feature that other mobile commerce competitors do not have. This cart feature makes the user's habits in using mobile commerce applications different and makes it easier for users to find out the entire item to be paid for. In addition, this feature can also assist users in making payments simultaneously for several orders. However, the user interface on the TravelAja application is still not good, and improvements are needed so that users will feel comfortable when using the application. The application needs to be analyzed first to find the problem. This is done to improve the user interface of the TravelAja application. This study uses the User Centered Design (UCD) method because this method places the user at the core of the whole process. This method begins with interviews with several respondents who usually use travel applications and have tried the TravelAja application to find out user problems. After the interview, the user is asked to assess the application's usability using the System Usability Scale (SUS). Furthermore, the repair process is carried out, and a prototype is obtained, which is then evaluated. Based on the evaluation results, the results of SUS were obtained with a grade of A+. It can be concluded that the prototype is excellent.